Undifferentiated (Anaplastic) Carcinoma of The Thyroid with Abundant Mucin Production: A Rare Presentation Causing Diagnostic Difficulty - Gaikwad, Vaishali; Baskaran, Sumitha; Gadgil, Nitin (Annals of Pathology and Laboratory Medicine, 2019)
Most pathologists are unaware that thyroid gland also produces mucin; often associated with typical thyroid carcinoma rather than primary mucinous neoplasm. We report an unusual case of anaplastic carcinoma of thyroid presenting with abundant extracellular mucin. A 65 year old lady presented with painless, neck swelling since 7-8 months. Thyroid function tests were within normal limits. Imaging suggested neoplastic aetiology of thyroid. Cytology revealed abundant extracellular mucin with occasional large atypical cells. Hence, metastasis followed by primary mucinous thyroid carcinoma was considered. After excluding secondary neoplasms, total thyroidectomy with lymphadenectomy was performed. Histopathology revealed an infiltrative tumour with abundant mucin & necrosis amidst fibrotic bands. Tumour cells were arranged in sheets, with features of anaplasia. Focus of papillary thyroid carcinoma also identified. Mucicarmine and Alcian blue special stains were positive. Immunohistochemistry results of positive cytokeratin and negative TTF1, thyroglobulin and calcitonin confirmed our results.